SAT0752-HPR The measurement of patients' expectations of a multidisciplinary and dedicated fibromyalgia program. (15th June 2017) - Xhaxho, D; Borg, AA; Mercieca, C
Abstract : Background: Fibromyalgia (FM) is a chronic and multidimensional condition impacting the physical health and psychosocial state of the individuals. In addition to performing clinical and psychological assessments, evaluating patients' expectations may help address their specific needs and improve outcomes. Objectives: The aim of this study was to assess the expectations of a cohort of FM patients participating in a multidisciplinary, dedicated fibromyalgia program. Methods: This was a survey of 86 consecutive FM patients who were initiating a multidisciplinary program delivered by a rheumatologist, nurse, physiotherapist, occupational therapist, psychotherapist and GP with a special interest in FM. Patients were diagnosed using the 2010 ACR diagnostic criteria. Demographic data, Widespread Pain Index (WPI), Symptom Severity Score (SSS) were recorded. Patients filled in the self-administered questionnaires including the Revised fibromyalgia impact questionnaire (FIQR), Hospital Anxiety and Depression Scale (HADS) and a patients' expectations questionnaire. The latter consisted of both open ended and closed questions using a five- point Likert scale (1=strongly agree to 5=strongly disagree) about the following domains; physical, psychological, coping and social aspects. Results: Eighty six patients (92% females) participated in the survey. The average age was 51.2 years (SD 10.60) and mean duration of symptoms 13.3 years (SD 11.17). The mean HADS-A was 11.6 (SD 4.37), HADS-D 8.67 (SD 3.47) and FIQR 55.9 (SD 21.64). In response to an open question about what was their main expectation from this program, just over half of the patients (52.3%) reported improvement of pain and fatigue as their most important outcome. This was followed by improved quality of life (19.3%), being able to cope better with ADLs, family and work (17.4%), obtain more knowledge about the condition (5.8%), while 15.1% did not have any expectations. When asked to rate their expectations for each specific domain: 64% expected significant improvement of physical symptoms, 74% to be able to cope better with family, hobbies and work and 66% expected an improvement of their psychological state, namely depression and anxiety. By the end of the program, 66% of the patients expected to have minimal or no symptoms. When asked to identify any lifestyle changes which could help, 30.2% mentioned a better work-life balance, 12.8% starting an exercise routine, 10.5% weight loss, 11.6% a mixture of house adaptations while 34.9% could not come up with any suggestions. Conclusions: Expectations of fibromyalgia patients were high in all domains. This study highlights the need for multidimensional assessment and a personalised treatment approach in managing fibromyalgia. Moreover, it is very important to assess patients' expectations in order to guide interventions and set realistic achievable goals which are acceptable to both patients and clinicians. Patients' expectations are an important patient reported outcome measure, which need to be assessed. References: Goffaux P, De Souza J, Potvin S, Marchand S(2009) Research papers: Pain relief through expectation supersedes descending inhibitory deficits in fibromyalgia patients. Pain 145:18–23. Hamnes B, Hauge M, Kjeken I, Hagen K (2011) ' I have come here to learn how to cope with my illness, not to be cured': A Qualitative Study of Patient Expectations Prior to a One-Week Self-Management Programme. Musculoskeletal Care 9(4):200–210. Disclosure of Interest: None declared